2014
DOI: 10.1021/am500429c
|View full text |Cite
|
Sign up to set email alerts
|

Stacked Quantum Dot Embedded Silica Film on a Phosphor Plate for Superior Performance of White Light-Emitting Diodes

Abstract: Application of quantum dots as a color converter in white light-emitting diodes (WLEDs) has been highly restrained because of its lower stability under the operating conditions of LEDs. The feasibility of using quantum dots in WLEDs has been studied and demonstrated by developing a non-conventional packing technique. Multiple core shell CuInS2/ZnS quantum dots were coated by silica, and the silica-coated quantum dots were dispersed in ethoxylated trimethylolpropane triacrylate to form a color conversion film. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 21 publications
0
45
0
2
Order By: Relevance
“…Meanwhile, Aboulaich et al had also realized WLED with CRI (Ra) of 84 and luminous efficiency of 30.6 lm/W at 20 mA by employing YAG:Ce phosphors and red CuInS 2 QDs as light convertors [10]. Moreover, Sohn et al [11] and Kim et al [12,13] had utilized bilayer structured QD-based light converting films to realize WLED with CRI (Ra) larger than 80 and luminous efficiency below 75 lm/W at 20 mA. The high performances were mainly contributed by the combination of various QDs or QDs and yellow phosphors, which composed the desired light converting material for the WLED.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Aboulaich et al had also realized WLED with CRI (Ra) of 84 and luminous efficiency of 30.6 lm/W at 20 mA by employing YAG:Ce phosphors and red CuInS 2 QDs as light convertors [10]. Moreover, Sohn et al [11] and Kim et al [12,13] had utilized bilayer structured QD-based light converting films to realize WLED with CRI (Ra) larger than 80 and luminous efficiency below 75 lm/W at 20 mA. The high performances were mainly contributed by the combination of various QDs or QDs and yellow phosphors, which composed the desired light converting material for the WLED.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize such issues, the hydrophobic ligands of QDs can be replaced with oligomeric or polymeric ligands containing functional anchor moieties (such as thiols, amines, or carboxylicgroups) which increase their miscibility with the polymer matrix [52]. Another common method is to protect QDs with an optically transparent barrier material such as silica, forming QDs-silica composite [53][54][55][56][57][58][59][60][61][62]. In the work of Ziegler et al [53], SiO 2 -coated red emitting InP/ZnS QDs were produced, showing excellent compatibility between the silica shell and silicone resin, thus forming homogeneous, stable, and transparent QDs-silicone composites.…”
Section: All-qd Based Wledsmentioning
confidence: 99%
“…[1][2][3][4] It is reported that the conventional way to fabricate white LEDs is based on a combination of blue LED and yellow phosphor of Y 3 Al 5 O 12 :Ce 3+ (YAG:Ce). [5,6] However, there are some shortcomings of such w-LEDs based on the combination such as low color rendering index (CRI) and highly correlated color temperature.…”
Section: Introductionmentioning
confidence: 99%